Reviving chickpea through integrated pest management in Nepal - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Farmers' participatory on-farm research and promotion was conducted in collaboration between the Nepal Agricultural Research Council(NARC), NGOs, Farmers’ Self Help Groups (FSHGs), International Agricultural Research Centers (IARCs), advanced research institutes and ICRISAT. To begin with, the concept and components of IPM of chickpea were discussed with farmers in several villages and several IPM orientation camps and schools were conducted during the crop season.